Continuous nitrogen-doped carbon nanotube matrix for boosting oxygen electrocatalysis in rechargeable Zn-air batteries - Chen, Guangda; Xu, Yangyang; Huang, Lei; Douka, Aboulkader Ibro; Xia, Bao Yu (Journal of energy chemistry, 2021)
Interconnected Carbon Nanotube Network: Continuous nanocarbon matrix composed of abundant interconnected nitrogen-doped carbon nanotubes demonstrates efficient and stable oxygen electrocatalysis for long-life rechargeable Zn-air batteries. [Display omitted] Developing robust oxygen electrocatalyst with high-performance is very significant for practical rechargeable Zn-air battery. We report herein the preparation of three-dimensional continuous nanocarbon network composed of interconnected nitrogen-doped carbon nanotubes and its application as oxygen electrocatalysis in rechargeable Zn-air battery. Except the excellent electrochemical bifunctionality, this carbon nanotube matrix also delivers an impressive battery performance. Specifically, an open-circuit voltage of 1.50 V as well as a high power density of 220 mW cm−2 with remarkable cycling stability for 1600 h is achieved in the rechargeable Zn-air battery. The study not only provides an efficient bifunctional oxygen electrocatalyst but more importantly may pave significant concepts in designing robust electrode for long-life rechargeable Zn-air battery and other energy technologies.